Simulated biological fluids – a systematic review of their biological relevance and use in relation to inhalation toxicology of particles and fibres. (16th March 2021) - Innes, Emma; Yiu, Humphrey H. P.; McLean, Polly; Brown, William; Boyles, Matthew
Abstract: The use of simulated biological fluids (SBFs) is a promising in vitro technique to better understand the release mechanisms and possible in vivo behaviour of materials, including fibres, metal-containing particles and nanomaterials. Applications of SBFs in dissolution tests allow a measure of material biopersistence or, conversely, bioaccessibility that in turn can provide a useful inference of a materials biodistribution, its acute and long-term toxicity, as well as its pathogenicity. Given the wide range of SBFs reported in the literature, a review was conducted, with a focus on fluids used to replicate environments that may be encountered upon material inhalation, including extracellular and intracellular compartments. The review aims to identify when a fluid design can replicate realistic biological conditions, demonstrate operation validation, and/or provide robustness and reproducibility. The studies examined highlight simulated lung fluids (SLFs) that have been shown to suitably replicate physiological conditions, and identify specific components that play a pivotal role in dissolution mechanisms and biological activity; including organic molecules, redox-active species and chelating agents. Material dissolution was not always driven by pH, and likewise not only driven by SLF composition; specific materials and formulations correspond to specific dissolution mechanisms. It is recommended that SLF developments focus on biological predictivity and if not practical, on better biological mimicry, as such an approach ensures results are more likely to reflect in vivo behaviour regardless of the material under investigation.